Coronavirus testing in women attending antenatal care. Issue 5 (September 2021) - Rolnik, Daniel L.; Korman, Tony M.; Rindt, Andrea; Stuart, Rhonda L.; Giles, Michelle L.; Rawlins, Janine; Palmer, Kirsten R.; Stripp, Andrew; Wallace, Euan M.; Hodges, Ryan J.
Abstract: Background: Universal screening has been proposed as a strategy to identify asymptomatic individuals infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and mitigate transmission. Aim: To investigate the rate of positive tests among pregnant women in Melbourne, Australia. Methods: We performed a cross-sectional prevalence study at three maternity hospitals (one tertiary referral hospital and two secondary maternities) in Melbourne, Australia. SARS-CoV-2 testing was offered to all pregnant women attending face-to-face antenatal visits and to those attending the hospital with symptoms of possible coronavirus disease, between 6th and 19th of May 2020. Testing was performed by multiplex-tandem polymerase chain reaction (PCR) on combined oropharyngeal and nasopharyngeal swabs. The primary outcome was the proportion of positive SARS-CoV-2 tests. Findings: SARS-CoV-2 testing was performed in 350 women, of whom 19 had symptoms of possible COVID-19. The median maternal age was 32 years (IQR 28–35 years), and the median gestational age at testing was 33 weeks and four days (IQR 28 weeks to 36 weeks and two days). All 350 tests returned negative results (p̂ = 0%, 95% CI 0–1.0%). Conclusion: In a two-week period of low disease prevalence, the rate of asymptomatic coronavirus infection among pregnant women in Australia during the study period was negligible, reflecting low levels of community transmission.